2022
DOI: 10.1007/s10072-022-06191-9
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of clinical intervention and nursing for patients with post-stroke dysphagia

Abstract: Post-stroke dysphagia (PSD) is a common and costly complication of stroke and is associated with increased mortality, morbidity, and hospitalization. Although most patients can spontaneously resume swallowing, there are still many patients who do not recover and even die. Despite multiple advances in the acute treatment and secondary prevention of stroke, the effective treatment of PSD remains a neglected area. Studies have shown that repair mechanisms of neurostimulation techniques and increased cortical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 89 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…For patients, the inclusion criteria were: (1) age ranging from 18 to 80 years; (2) with a tracheostomy tube; (3) not mechanically ventilated; (4) without require-ments for supplementary oxygen; (5) manifesting as aspiration (penetration-aspiration scale (PAS) score ≥ 5). The exclusion criteria were: (1) unstable vital signs; (2) severe cognitive impairment; (3) a poor motor function that cannot cooperate with the inspection and evaluation; (4) previous diagnosis of dysphagia; (5) a history of seizure; (6) allergy to iohexol injections; (7) any neuropsychiatric comorbidity, affective disorder, or other respiratory diseases that may influence the test outcomes. For healthy participants, the inclusion criteria were: (1) age range from 18 to 80 years.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients, the inclusion criteria were: (1) age ranging from 18 to 80 years; (2) with a tracheostomy tube; (3) not mechanically ventilated; (4) without require-ments for supplementary oxygen; (5) manifesting as aspiration (penetration-aspiration scale (PAS) score ≥ 5). The exclusion criteria were: (1) unstable vital signs; (2) severe cognitive impairment; (3) a poor motor function that cannot cooperate with the inspection and evaluation; (4) previous diagnosis of dysphagia; (5) a history of seizure; (6) allergy to iohexol injections; (7) any neuropsychiatric comorbidity, affective disorder, or other respiratory diseases that may influence the test outcomes. For healthy participants, the inclusion criteria were: (1) age range from 18 to 80 years.…”
Section: Subjectsmentioning
confidence: 99%
“…ABI is defined as brain injuries caused by strokes, trauma, cerebral anoxia, tumors, or infections, which heavily impact the patient's quality of life and increase the economic burden [6]. The neurophysiological changes following ABI usually lead to aspiration [7]. In addition, tracheostomy is usually performed in patients requiring prolonged mechanical ventilation during the first days after the acute event, which causes decreases in the strength of sensory input and disuse atrophy of laryngeal structures [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that CPGs can improve health care (Lin et al, 2020; Tyagi & Dhesy‐Thind, 2018). Nurses, who identify dysphagia and coordinate multidisciplinary cooperation, are one of the health professionals promoting the rehabilitation of dysphagia (Fang et al, 2022). However, compared with physicians, nurses usually have a lower perception towards CPGs (Amer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, China's community rehabilitation medical resources are in relative shortage, especially professional physiotherapists in the community. This leads to the lack of professional home-based rehabilitation guidance for discharged PSD patients, making the rehabilitation effect of most discharged PSD patients unsatisfactory ( 19 ).…”
Section: Introductionmentioning
confidence: 99%